Letter from Carl D. Duncan to Patricia Whiting, July 1, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan opens the letter describing the field studies happenings. He collected pine cones for or Doris. The letter concludes with a brief discussion on and a copy of the revision of "Relaxation Suggestions" written by Duncan.